2015
DOI: 10.1002/pat.3648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization nanocomposite of polyacrylamide-rGO-Ag-PEDOT/PSS hydrogels by photo polymerization method

Abstract: We present a novel approach to the fabrication of advanced polymeric nanocomposite hydrogels from polyacrylamide (PAAm) by incorporation of graphene-silver-polyethylenedioxythiophene-polystyrene sulfonate (rGO-Ag-PEDOT/PSS) by photopolymerization method. Infrared spectroscopy was employed to characterize the structure of the hydrogels. The internal network structure of nanocomposite hydrogels was investigated by scanning electron microscope. Swelling, deswelling, and mechanical properties of the hydrogels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Lim et al reported fabrication of nanocomposite hydrogels from polyacrylamide (PAAm) along with RGO, Ag nanoparticles, and polyethylenedioxythiophenepolystyrenesulfonate mixture (PEDOT/PSS) by photopolymerization method. 421 The gel-nanocomposite showed improved mechanical, thermal, and electrical properties [e.g., compressive strength increased 1.57 times upon incorporation of 0.3 wt % of nanomaterials (RGO-Ag-PEDOT/PSS) and the electrical conductivity of the composite hydrogel appeared at 3.91 × 10 −5 S cm −1 ]. In another report, Banerjee and co-workers also reported sunlight induced in situ preparation of silver nanoparticles inside hydrogel network composed of GO or RGO in the presence of small molecular gelator 100 which constitutes trinanohybrid system.…”
Section: Applications Of Gel-nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al reported fabrication of nanocomposite hydrogels from polyacrylamide (PAAm) along with RGO, Ag nanoparticles, and polyethylenedioxythiophenepolystyrenesulfonate mixture (PEDOT/PSS) by photopolymerization method. 421 The gel-nanocomposite showed improved mechanical, thermal, and electrical properties [e.g., compressive strength increased 1.57 times upon incorporation of 0.3 wt % of nanomaterials (RGO-Ag-PEDOT/PSS) and the electrical conductivity of the composite hydrogel appeared at 3.91 × 10 −5 S cm −1 ]. In another report, Banerjee and co-workers also reported sunlight induced in situ preparation of silver nanoparticles inside hydrogel network composed of GO or RGO in the presence of small molecular gelator 100 which constitutes trinanohybrid system.…”
Section: Applications Of Gel-nanocompositesmentioning
confidence: 99%
“…Thus, the gel-nanocomposite showed good photocatalytic performance for the removal of dyes such as Rhodamine B and methylene blue in single or mixed solutions. Lim et al reported fabrication of nanocomposite hydrogels from polyacrylamide (PAAm) along with RGO, Ag nanoparticles, and polyethylenedioxythiophene-polystyrenesulfonate mixture (PEDOT/PSS) by photopolymerization method . The gel-nanocomposite showed improved mechanical, thermal, and electrical properties [e.g., compressive strength increased 1.57 times upon incorporation of 0.3 wt % of nanomaterials (RGO-Ag-PEDOT/PSS) and the electrical conductivity of the composite hydrogel appeared at 3.91 × 10 –5 S cm –1 ].…”
Section: Applications Of Gel-nanocompositesmentioning
confidence: 99%
“…Briefly, the Ag-graphene hybrid composite wassynthesized as follows [49]: A uniform aqueous solution of graphene oxide (GO) was obtained when 50 mg of GO was dispersed in deionized water and sonicated for about 3 h, reaching a concentration up to 1 mg/mL. A total of 100-300 mg of silver nitrate (AgNO 3 ) was dissolved into 10 mL of deionized water and transferred to 30 mL ethylene glycol.…”
Section: Synthesis Of Ag/rgo Hybrid Compositementioning
confidence: 99%
“…Polyacrylamide (PAAM) hydrogel is a hydrophilic polymer that can absorb large amounts of water while maintaining its structural integrity ( Azar et al, 2021 ; Ohm et al, 2021 ). PAAM hydrogel has the following advantages ( Lim et al, 2016 ; Gan et al, 2018 ; Sun et al, 2021 ): a) High elasticity: PAAM has high elasticity and can withstand certain tensile and compressive stresses without breaking; b) Flexibility: PAAM has good flexibility and can adapt to wounds of different shapes and its flexibility also makes it easier to apply to uneven or curved wound surfaces ( Kim et al, 2016 ); c) Favorable adhesion: PAAM can form good adhesion on the wound surface, which allows the gel to remain on the wound surface so that it is not easy to slip; d) Acceptable biocompatibility: PAAM has good biocompatibility and can seamlessly connect with surrounding tissues without excessive inflammation or rejection ( Ohm et al, 2021 ). MXene is an emerging two-dimensional material that can be used to prepare hydrogels due to its unique chemical composition and structural characteristics ( Wang et al, 2019 ; Chen et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%